Cobra 40 jaar later : Collectie J. Karel P. Van Stuijvenberg - Kossmann, E.H.; Stokvis, Willemijn; Birtwistle, Graham; Wijnants, Tania; van de Watering, C.E.; Wingen, Ed ('s-Gravenhage : Sdu uitgeverij, 1988)
Alechinsky, Pierre ; Appel, Karel ; Atlan, Jean Michel ; Balle, Mogens ; Bille, Ejler ; Brands, Eugene ; Bury, Pol ; Collignon, Georges ; Constant ; Corneille ; Cox, Jan ; Dotremont, Christiaan ; Doucet, Jacques ; Ferlov, Sonja et al.
Cobra 40 jaar later, De Nieuwe Kerk, Amsterdam, van 9 november tot en met 31 december 1988
boek